Social responsibility approach as an explanatory model for the solution to squatter settlements using the example of Mwanza City, Tanzania - Sakina, Faru (International Journal of Emerging Trends in Social Sciences, 2024)
The purpose of this study was to provide reinforcement to solutions aimed at resolving problems brought about by squatter settlements in Mwanza city, Tanzania. In its pursuit, this study employed Social Responsibility Approach as an explanatory model for strengthening sought solutions to squatter settlements in Mwanza city, Tanzania. Qualitative research approach through a case study strategy was mainly employed with minimum quantitative research approach. Purposive sampling to get government leaders was used, while simple random sampling was employed to obtain respondents in squatter settlements for the study. Data collection methods included questionnaire, semi-structured interview and focus group discussions that yielded primary data, whereas documentary review furnished secondary data. Qualitative data were subjected to content analysis, while quantitative data were subjected to statistical analysis. Results from this study indicate that there was no individual and civil society involvement in dealing with squatter settlement problems. Besides, there are several difficulties including people’s hardships in squatter areas; big population increase; unscrupulous house construction; and political leaders’ failure to control as well as prevent squatters. There are government initiatives in dealing with squatter settlements but all are mainly executed through top-down approach that has no achievements. The employed Social Responsibility Approach in uncovering pertinent pathways as solutions to squatter settlement is important because it recommends for use of bottom-up approach instead of top-down approach owing to the fact that the latter has never yielded positive results in solving squatter settlement problems.